INSPIRING REMOTE TECH TEAMS keys to leadership and purposeful performance. - Smith, Hubbert ([S.l.] : AUERBACH PUBLICATIONS, 2021)
For me and other tech people, leaders, and members of remote teams, we will be awakened by all the fantastic hands-on hints, best practices, and guiding principles based on solid ground that Hubbert provides in Inspiring Remote Tech Teams. We will be better prepared and better equipped to both contribute and lead efficiently in the digital economies that shape the future of our world. -- Thomas DiGiacomo, President of Engineering and Innovation at SUSE Inspiring Remote Tech Teams is a trail map to building effective teams and organizations--now, as world health dictates remote work, and in the future, as global talent pools contribute to our digital economy. Humans are wired to be social, and world events require social distancing from our office community. The absence of "community" triggers primitive brain responses. These instinctual responses of survival, social belonging, and the power of story all profoundly surface during our reaction as we adjust to remote work. This trail map for team leaders improves team execution despite physical separation. The book covers simple neuroscience as it applies to our "separation." It is a hands-on guide to maintaining and improving teamwork while working remotely. It is also a hands-on guide at the intersection of teams + remote + laymen's neuroscience to create a positive sense of enthusiasm, engagement, and contribution, even when working apart. Remote teams, now and for the future, are the pathway to using global talent effectively. This book examines the combination of the "hard skills" of tech team project management and the "soft skills" of healthy distributed teams: remote offices, sales offices, partners, suppliers, customers, and teams engaging global talent pools. Practical examples and best practices offer hands-on methods to use neuroscience to help teams be their best, to improve collaboration, and to deliver consistent team results.
OCLC-licensed vendor bibliographic record.
Keywords: Virtual work teams -- Management